Hardening characterisation of a non-proprietary and more eco-friendly UHPC - Matos, Ana Mafalda (2023)
The current work provides an integrated analysis of autogenous shrinkage, isothermal calorimetry, and modulus of elasticity measurement through ambient response method (EMM-ARM), to characterise the hardening behaviour of a non-proprietary and more eco-friendly ultra-high performance fibre reinforced cementitious composite (UHPFRC). Isothermal calorimetry revealed that induction period ends at 3 h, and the rapid evolution of hydration heat occurs up to 9 h. Then, the hydration reaction still undergoes but at a very slow rate. The autogenous shrinkage exhibited a strong increase, particularly in the first 6 h, after which a dramatic reduction in the slope of the curves occurred, corroborating with the heat of hydration measurements. The modulus of elasticity evolution pattern revealed a typical cementitious material S-shaped curve, with a strong evolution in the first 8 h and reached 37 GPa at 7 days. As the current study perceives, UHPC/UHPFRC-3 % MOE evolution mainly occurs at very early ages. Thus, using EMM-ARM method for evaluating stiffness-related properties since casting age of UHPC/UHPFRC is of utmost importance to take advantage of the remarkable properties of such advanced material with no waste of time and resources. Furthermore, the UHPFRC developed with a lower amount of cement and silica fume decreases the heat of hydration, shrinkage, and reduced costs and ecological footprint without significantly impairing the MOE, compared to other non-proprietary blended UHPC/UHPFRC mixtures.